Synthesis and Characterization of Nata de Coco Based Edible film with the Addition of Cinnamon Oil - Dwi Ayu Stephanie; Marfuatun Marfuatun; Imam Arifin (CHEMICA: Jurnal Teknik Kimia, 2021)
The edible film is an alternative packaging with renewable and safe materials. The edible film used is methylcellulose from nata de coco with polyvinyl alcohol (PVA) plasticizers and cinnamon oil additives. This research aimed to determine the effect of PVA on the mechanical properties of edible film and the effect of adding cinnamon oil on the character of edible film. PVA added were 5%, 10%, 15%, 20%, 25% and cinnamon oil added were 2%, 4%, 6%, 8%, 10%. The mechanical properties of the edible film were observed by tensile strength tester, whereas water vapor absorption by gravimetric method. The result showed the optimum mechanical properties of the edible film was addition PVA 15% which was 1.565 MPa. The more cinnamon oil was added, the mechanical properties of edible film tend to decrease, however, the water vapor absorption tends to increase. The addition of cinnamon oil also showed antimicrobial activity that the fungus did not grow on the edible film.